Elemen pembentuk citra kota dalam kawasan stasiun kereta api di Kota Semarang - Unsani Lutfiana; Siti Rukayah (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Transportation is an important part of urban development so that the existence of transportation service places is also quite vital, one of which is the train station area. The train station area has its own characteristics, character, and identity so that it can shape the image of the area. According to Kevin Lynch (1960), a city image contains elements that form the city's image in the form of paths, edges, district s, nodes, and landmarks. Semarang City has two main stations, namely the Semarang Tawang Station area and the Semarang Poncol Station area. The existence of the two train station areas is important so that it is necessary to understand theelements that form the city's image in order to obtain clarity on its identity and character. The research method used is qualitative research in the form of a case study approach with primary and secondary data. The results of this study are in the form of identification of elements that form the city's image in the Semarang Tawang Station area and the Semarang Poncol Station area, where elements are still found that are less appropriate and can still be improved or developed in order to strengthen the identity and character of the train station area